The prevalence and characterization of self‐perceived sensitive facial skin among Freshmen in Urumqi, China. (28th September 2021) - Feng, Yanyan; Shi, Qun; Ding, Yuan; Xiang, Fang; Liu, Jianyong; Yu, Junfeng
Abstract: Background: The clinical signs, symptoms, and the etiology of sensitive skin (SS) in general populations have been extensively studied over the last decades, but the characteristics of SS in Xinjiang, particularly the age‐related characteristics, still remain unknown. Objective: This study aimed to characterize the SS facial skin in normal adolescents of Xinjiang. Methods: A questionnaire was developed based on SS and given to each participant. The clinical signs, symptoms, associated trigger factors, and DQLI of facial SS were compared in normal young Chinese males versus females. Results: A total of 3584 freshmen were investigated, wherein 83 were diagnoses as self‐reported facial SS (2.3%). The prevalence of SS was found to be significantly higher in females than in males. Spicy food, mood change, and skin care products are the major contributors to facial SS ( p < 0.01). Moreover, family history and sun exposure are closely related to the onset of SS ( p < 0.05). More SS patients were sensitive to emotional factors and had a greater difficulty with shopping or housework, dressing, socializing, or other leisure activities. The main manifestations of SS are flushing, erythema, and dry skin on buccal, frontal, and temporal sputum. The symptoms mainly include skin burning and dry itching, and two or more symptoms at the same time. The absolute value of red area and pores of SS were higher than that of normal skin ( p < 0.05). Conclusions: The prevalence, symptoms, clinical characteristics, and triggering factors of facial SS in normal young of Xinjiang, especially freshmen in the 17–21 age group, were not similar with SS, which might be due to racial and regional differences.